NOMOKRASI ISLAM DAN NEGARA KESATUAN REPUBLIK INDONESIA (NKRI) DALAM HUKUM TATA NEGARA - Rangkuti, Afifa (AS-SAIS (JURNAL HUKUM TATA NEGARA/SIYASAH), 2017)
As a country with the greatest Muslim population in the world, it does not make Islam its ideology. In the form of relationship how Islam and the Unitary State of the Republic of Indonesia can be realized. This classic problem still requires special attention, because the debate is always inviting Reaction and action. Islam as a religion is seen as a system of living systems that are complex and capable of being believed to be a powerful mechanism in dealing with various problems of life encountered. Shari'ah is composed of a mixture of pre-Islamic customs and customs with principles and laws derived from authentic Qur'an and Hadith. Islamic thinkers seek to become Islamic teachings of ethical and national policy. Nevertheless, the principle of the state of Indonesia is accepted as final, but until now the conflict between Islamic identity and Indonesia is contested, albeit on a lesser scale.Keyword: Nomocracy Islam, United States of Indonesian Republic, Constitutional Law.